2020
DOI: 10.21666/muefd.637421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Test Anxiety in High School and Universıty Students

Abstract: Özet Sınav kaygısı eğitim hayatının göz ardı edilemez fenomenlerinden birisidir. Sınav kaygısının lise öğrencilerde mi üniversite öğrencilerinde mi daha yüksek olduğunu belirlemek üzere tasarlanan bu çalışma, Muğla ilindeki 3 lise ve Muğla Sıtkı Koçman Üniversitesi Eğitim Fakültesi öğrencileri üzerinde gerçekleştirilmiştir. Katılımcıların 262'si üniversite, 415'i lise öğrencisidir. Araştırmada Westside Sınav Kaygısı Envanterinin lise ve üniversite öğrencileri için olan versiyonları kullanılmıştır. Sınav kaygıs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
2
1
Order By: Relevance
“…In a previous study conducted with 1.021 students during the Covid‐19 lockdown, it was reported that the anxiety level of students preparing for the university exam is quite high compared to students studying at university (Fernández‐Castillo, 2021). However, in contrast to earlier findings, a previous study stated that university students have higher exam anxiety than high school students (Doğan, 2020). During the Covid‐19 lockdown, we found that students preparing for the university exam had higher exam anxiety in both groups, but higher in the high school graduate than HS.…”
Section: Discussioncontrasting
confidence: 94%
“…In a previous study conducted with 1.021 students during the Covid‐19 lockdown, it was reported that the anxiety level of students preparing for the university exam is quite high compared to students studying at university (Fernández‐Castillo, 2021). However, in contrast to earlier findings, a previous study stated that university students have higher exam anxiety than high school students (Doğan, 2020). During the Covid‐19 lockdown, we found that students preparing for the university exam had higher exam anxiety in both groups, but higher in the high school graduate than HS.…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, women experience more exam anxiety than men (Kumaran & Kadhiravan, 2015; Trifoni & Shahini, 2011). Moreover, exam anxiety was found to be greater among college students compared to high-school students (Doğan, 2020). Therefore, it can be argued that both proximal and distal systems, personality characteristics, and time factors are effective in exam anxiety.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the study conducted by Balat and Akman on high school students in 2004, no difference was found between male and female students in terms of self-esteem levels. In the studies conducted by Erbil et al in 2006, Sprecher et al in 2013, and Doğan et al in 2009 significant difference was found between the self-esteem of male and female students. In his study in 2015, Sarıkaya said; found that self-esteem was higher in male students.…”
Section: Conclusion and Discussionmentioning
confidence: 92%